Linking major depressive disorder pathogenesis with kynurenine pathway - a literature review - Szawica, Dominik; Kuźniar, Aleksandra; Fularska, Kamila; Oleszko, Michał; Wąsiewicz, Edward (Journal of Education, Health and Sport, 2023)
Introduction: Depressive disorders are a significant problem. They lead to suffering, loss of interest and may contribute to suicide attempts. Despite the large number of available medications, 10-35% of patients fail to achieve remission. Therefore, for these ongoing researches are underway to thoroughly understand the pathophysiology of depression. Aim of study: The purpose of the study was to review the latest literature on the kynurenine pathway importance in depression, and to discover its links with theories relating to the pathogenesis of depression. Matherials and methods: A systemic review was conducted using PubMed, ScienceDirect, Google Scholar databases and it was limited to studies published between 2000 and 2023. The search strategy was based on following terms: kynurenine, depression, kynurenine pathway in depression, treatment resistant depression, tryptofan metabolites. Results: Animal studies confirm the importance of the kynurenine pathway in animal models of depression. Peripherally directed inflammatory stimuli in humans lead to peripheral activation of the kynurenine pathway. The regulation of the kynurenine pathway in the brain is specific to a particular region as well as to a given type of depression.Conclusions: Further studies of the kynurenine pathway targeting different regions of the brain are necessary. Conducting a simultaneous analysis of many central and peripheral tryptofan metabolites will be helpful to accurately determine their mutual impact in both compartments. Understanding changes in kynurenine pathway transmission in a particular type of depression may be helpful in developing new, more effective drugs.